2017
DOI: 10.21873/anticanres.11879
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Stimulates the Function of Natural Killer Cells in Different Experimental Settings

Abstract: Lidocaine showed an important stimulatory activity on NK cells. Our findings suggest that lidocaine might be used perioperatively to minimize the impact of surgery on NK cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Clinically achievable concentrations of lidocaine may also benefit CMI by enhancing the cytotoxic effects of NK cellsin vitro NK cytotoxicity against leukaemia cells was promoted by lidocaine treatment (at 0.01µM to 50µM), an effect attributed experimentally to enhanced lytic granule release (150). Similar NK cytotoxicity enhancement was identified in a study which isolated NK cells from healthy donors and cancer patients (both pre-and post-operatively) -NK cells treated in vitro with lidocaine had greater cytotoxic effects against cancer cells (151).…”
Section: Effects On Immune Cellsmentioning
confidence: 63%
“…Clinically achievable concentrations of lidocaine may also benefit CMI by enhancing the cytotoxic effects of NK cellsin vitro NK cytotoxicity against leukaemia cells was promoted by lidocaine treatment (at 0.01µM to 50µM), an effect attributed experimentally to enhanced lytic granule release (150). Similar NK cytotoxicity enhancement was identified in a study which isolated NK cells from healthy donors and cancer patients (both pre-and post-operatively) -NK cells treated in vitro with lidocaine had greater cytotoxic effects against cancer cells (151).…”
Section: Effects On Immune Cellsmentioning
confidence: 63%
“…In this regard, lidocaine can modulate several mechanisms involved in cancer cell survival and proliferation as well as enhance the effect of cells involved in immune surveillance. For instance, lidocaine inhibits the invasion and migration of ovarian cancer ES-2 cells, exhibits antiangiogenic effects and stimulates the cytotoxic function of natural killer cells at lower than clinical concentrations (8,17,18). Last, lidocaine is an inhibitor of voltage-gated sodium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have also confirmed this finding in a randomized controlled trial (RCT) where intravenous lidocaine was associated with significantly less production of IL-1ra, IL-6 with preservation of the lymphocyte proliferation ( 105 ). Lidocaine has also stimulated the function of NK cells of patients undergoing cancer surgery ( 106 ). Recently, a RCT looking at the effect of intravenous lidocaine infusion in breast cancer patients demonstrated a decrease in postoperative expression of NETosis (which is associated with disease progression) and MMP3 ( 107 ).…”
Section: Inhalational Agents and Intravenous Anesthetics For Cancer Surgerymentioning
confidence: 99%